2018
DOI: 10.12968/bjnn.2018.14.2.58
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy: pathophysiology, clinical manifestations and treatment options

Abstract: Epilepsy is a global health problem affecting approximately 50 million people worldwide. It is one of the most common chronic neurological diseases in the world with serious physical, economic and discriminatory consequences in some parts of the world. However, the healthcare burden and financial cost of treating epilepsy can be reduced with appropriate and prompt interventions. Although epilepsy and its treatment are complex, current evidence suggest insufficient knowledge of seizure classification and a gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…This tool was based on current clinical evidence. 19,20 The 10 multiple-choice knowledge questions were related to seizure pathophysiology, seizure etiology, focal seizure with impaired awareness, VEEG safety, VEEG purpose, epilepsy classification, generalized versus focal seizure, consciousness assessment, language assessment, Time to testing after seizure alarm improved from 30.5 to 14 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…This tool was based on current clinical evidence. 19,20 The 10 multiple-choice knowledge questions were related to seizure pathophysiology, seizure etiology, focal seizure with impaired awareness, VEEG safety, VEEG purpose, epilepsy classification, generalized versus focal seizure, consciousness assessment, language assessment, Time to testing after seizure alarm improved from 30.5 to 14 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…The brain is responsible to control the activity of neurons, nerve cells which specially designed to channel electrical impulses around the central and peripheral nervous systems [ 35 ]. A seizure developed when an abnormal synchronous firing of neurons in some parts of the brain occurs [ 36 ].…”
Section: The Pathophysiology Of Epilepsymentioning
confidence: 99%
“…Approximately 50 million individuals worldwide sufer from epilepsy, which is a serious global health issue. It is one of the most widespread chronic neurological conditions in the world and, in some regions, has detrimental physical, fnancial, and discriminatory effects [2]. After a stroke and Alzheimer's disease, epilepsy is the third most frequent neurological condition [3].…”
Section: Introductionmentioning
confidence: 99%
“…Genetic epilepsy results from a genetic predisposition of the brain to produce seizures, while acquired epilepsy is due to acute insult or a lesion that alters the cellular, molecular, and physiological properties that give origin to seizures [4]. It has been suggested that altered neuronal membrane permeability, decreased inhibitory neuronal regulation, or neurotransmitter imbalance may be the probable initiators of seizures, though the precise cellular efect is not fully clear [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation